The Sortino framework for constructing portfolios : focusing on desired target return to optimize upside potential relative to downside risk - Sortino, Frank Alphonse, 1932- (Elsevier finance., 2010)
The most common way of constructing portfolios is to use traditional asset allocation strategies, which match the client's risk appetite to a weighted allocation strategy of fixed income, equities, and other types of assets. This method focuses on how the money is allocated, rather than on future returns. The Sortino method presents an innovative change from this traditional approach. Rather than using the client's risk as the main factor, this method uses the client's desired return. The goal is what the investor is trying to accomplish financially, such as a certain level of income in retirement or putting children through college. .Feature: Only book to describe the Sortino method and Desired Target ReturnT in a way that enables portfolio managers to adopt the method. .Benefit: Gives a new way of constructing portfolios into the hands of portfolio managers .Feature: Software to implement the portfolio construction method is included free of charge to bookbuyers on a password protected Elsevier website .Benefit: Book buyers can use the software to construct portfolios using this method right away, in real time. They can also load in their current portfolios and measure them against these measures. .Feature: The Sortino method has been tested over 20 years at the Pension Research Institute .Benefit: Portfolio managers can be confident of the success of the method, even returns in the economic crisis, where the method has still beaten all S & P benchmarks.